REKOMENDASI KEBIJAKAN MODEL PEMBELAJARAN PENDIDIKAN DI KABUPATEN MALANG - Dwinugraha, Akbar Pandu (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2023)
This study aims to provide policy recommendations on learning models after the decline in Covid-19 transmission in Malang Regency. This research uses a combination of qualitative and quantitative research. The research location covers all elementary and junior high schools in Malang Regency spread across 33 sub-districts. The results of the study found that the learning process carried out in Malang Regency at the beginning of the decline in the transmission of the Covid-19 pandemic was a combination of online and offline. The problems faced when learning has taken place in a combination of offline and online are dominated by the limited ownership of online learning media by students. On the other hand, when offline, the interaction and activity of students is low, which is motivated by online learning habits with a very different environmental situation from in the classroom in person. So there was a gap between offline learning and online learning. This gap is found when learners have done offline learning. Based on these conditions, policy recommendations for the form of a learning model based on current conditions are formulated. This model is a constructively constructive recovery of instructive offline learning. The success of this model depends on the cooperation between students, teachers, parents and the government.